Development of risk-targeted seismic hazard maps for low-rise and mid-rise reinforced concrete buildings in the Philippines - Mallari, Royce Argel N.; Garciano, Lessandro Estelito O.; Peñarubia, Henremagne C. (2023)
The seismic hazard maps of the Philippines provide spectral acceleration mean values that describe the probability of occurrence of area-specific ground motion hazards due to earthquakes in the country. However other countries have progressed from developing hazard maps to risk-targeted maps that include information on the probability of collapse of buildings. This is the research gap that this study aims to bridge and, thus, developed maps of risk-targeted ground motions (RTGM) for the Philippines using the City of Manila as the area of focus. The maps will be created using the procedure suggested in ASCE 7-16 in obtaining the risk-targeted maximum considered earthquake (MCER). The probabilistic MCER will be created using the information obtained from the seismic hazard and the generic fragility curve that will represent the performance of buildings during a maximum considered earthquake (MCE) event. In this study, the seismic hazards were obtained using the same procedure, decision-making, and empirical formula as the one used in developing the Spectral Acceleration Maps of the Philippines (SAM PH). While the generic fragility curve was
described by a function with a lognormal standard deviation, β, of 0.7. With a considered risk level of 1% probability of collapse in 50 yr, the developed RTGM maps are presented in this study. In the analysis of results, the probabilistic MCER is lesser than the MCE level spectral accelerations in the majority of the area in Manila due to the influence of the building’s collapse capacity for stiff soil profiles. The opposite can be seen in softer soil profiles. However, the final MCER values are slightly larger than the MCE values due to the application of the directivity factors.
Keywords: Earthquake simulators